Calculate: (4(3-x))/(2)+3=-x+3

Expression: $\frac{ 4\left( 3-x \right) }{ 2 }+3=-x+3$

Cancel equal terms on both sides of the equation

$\frac{ 4\left( 3-x \right) }{ 2 }=-x$

Cancel out the common factor $2$

$2\left( 3-x \right)=-x$

Distribute $2$ through the parentheses

$6-2x=-x$

Move the constant to the right-hand side and change its sign

$-2x=-x-6$

Move the variable to the left-hand side and change its sign

$-2x+x=-6$

Collect like terms

$-x=-6$

Change the signs on both sides of the equation

$x=6$